Impact of COVID-19 on college students at one of the most diverse campuses in the USA: a factor analysis of survey data. Issue 9 (5th September 2022) - Liu, Bowen; Huynh, Edward; Li, Chengcheng; Wu, Qing
Abstract : Objective: This survey study is designed to understand the impact of the COVID-19 pandemic on stress among specific subpopulations of college students. Design, settings and participants: An online questionnaire was sent to the students from University of Nevada, Las Vegas, between October 2020 and December to assess the psychological impact of COVID-19. A total of 2091 respondents signed the consent form online and their responses were collected. Main outcome measures: Measures of psychological stress, as prescribed by the Perceived Stress Scale (PSS-10). An explanatory factor analysis was carried out on the PSS-10 results. We subsequently analysed each factor using stepwise linear regression that focused on various sociodemographic groups. Results: A two-factor model was obtained using the explanatory factor analysis. After comparing with the past studies that investigated the factor structure of the PSS-10 scale, we identified these two factors as 'anxiety' and 'irritability'. The subsequent stepwise linear regression analysis suggested that gender and age (p<0.01) are significantly associated with both factors. However, the ethnicities of students are not significantly associated with both factors. Conclusions: To our knowledge, this is the first study that assessed the perceived stress of university students in the USA during the COVID-19 pandemic. Through exploratory factor analysis, we showed that the PSS-10 scale could be summarised as a two-factor structure. A stepwise regression approach was used, and we found both of the factors are significantly associated with the gender of the participants. However, we found no significant association between both factors and ethnicity. Our findings will help identify students with a higher risk for stress and mental health issues in pandemics and future crises.